Вариант "Альфа": [роман] / Сергей Москвин ; [оформление художника М. Левыкина] - Москвин Сергей Львович (Группа Антитеррор, 2003)
Экземпляры: Ф--16 (20210705) / Инвентарный номер: 96675 / Цена: / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 82 / ББК: 84(2=411.2)6-44